Perananan Analisa Rasio Keuangan Dalam Memenuhi Standar Rasio Keuangan Kesehatan Perusahaan - Dewi Mayasari; Rini Yulia; Dona Marvita Rais (GLOBAL SCIENTS PUBLISHER, 2026)
This study assesses the health level of distributors in PT. Igasar from 2014 to 2016. The purpose of this study is to determine the level of health of the company. Sample in this research is financial report of PT. Igasar in 2014 to 2016. Data collection techniques in this study is descriptive method of analysis by using company documentation in the form of financial statements of the company. Data analysis used in this research is ratio analysis and financial report comparison analysis. The results of this study indicate that the health level of PT. Igasar in three consecutive years from 2014 to 2016 in terms of liquidity, both from the cash ratio and quick ratio has not been able to meet the standard financial ratios, so including the unhealthy category. Then in terms of solvency, both from the debt to asset ratio and debt to equity ratio shows a high figure. The high number of firm solvency ratios which indicates high corporate liabilities, as well as this ratio has not been able to meet the standard sound financial ratios. In terms of firm profitability, the ratio of nett profit margin and return on asset and return on equity also indicates that the figure still does not meet the standard figure of healthy financial ratio.